Improved Insulin Sensitivity With Angiotensin Receptor Neprilysin Inhibition in Individuals With Obesity and Hypertension. Issue 2 (17th November 2016) - Jordan, J; Stinkens, R; Jax, T; Engeli, S; Blaak, EE; May, M; Havekes, B; Schindler, C; Albrecht, D; Pal, P; Heise, T; Goossens, GH; et al.
Abstract : Natriuretic peptide (NP) deficiency and sustained renin‐angiotensin system activation are associated with impaired oxidative metabolism and predispose to type‐2 diabetes. We hypothesized that sacubitril/valsartan (LCZ696), which augments NP through neprilysin inhibition while blocking angiotensin II type‐1 (AT1 )‐receptors, improves insulin sensitivity, lipid mobilization, and oxidation. After 8 weeks of treatment of obese patients with hypertension, sacubitril/valsartan 400 mg q.d., but not amlodipine 10 mg q.d., was associated with a significant increase from baseline in the insulin sensitivity index (hyperinsulinemic‐euglycemic clamp), and tended to be higher in patients treated with sacubitril/valsartan compared to amlodipine. Abdominal adipose tissue interstitial glycerol concentrations increased with sacubitril/valsartan, but decreased with amlodipine. Whole‐body lipolysis and substrate oxidation did not change with either treatment. Results confirm that sacubitril/valsartan treatment leads to a metabolic benefit in the study population and supports the relevance of neprilysin inhibition along with AT1 ‐receptor blockade in the regulation of human glucose and lipid metabolism.